Piano sonatas by South African composers, 1900-2015: a catalogue and compositional analyses of selected works - Delport, Wilhelmus (College of Music, 2020)
The piano sonata’s prominent position in Western art music is reflected in both its long history and its presence in the oeuvres of composers from across the globe. While some information on piano sonatas by South African composers has been included in academic literature, no comprehensive research has been done in the field. This lacuna is addressed in this thesis of which the main research strategy is analytical, without precluding other data-collection methods such as literature studies, archival research and consultation with composers. The thesis comprises an introductory chapter with background information and an outline of the principal research aim and objectives; a general literature review of scholarly work in the field; a summary of academic literature on solo piano sonatas by South African composers; detailed analyses of two recent and diametrically opposed 21st-century solo piano sonatas, by Hendrik Hofmeyr (1957- ) and Graham Newcater (1941- ) respectively; and a final chapter with concluding remarks. Detailed catalogues of sonatas by South African composers, for piano as well as for other instruments, are included as appendices. Findings show that in correspondence with international trends, the piano sonata has held a prominent role in South African music-making with more than 230 works completed since 1900. A chronological estimation shows a more-or-less gradual increase in the number of sonatas composed up to 1975. 30 works were finalised between 2006 and 2015, suggesting that many contemporary composers continue to reference sonata structures as a guiding principle in largescale forms. The characteristics of the majority of sonatas analysed and those discussed in the literature summary correlate to some extent with 19th- and 20th-century traditions. There are nevertheless also various exceptions and novel explorations of traditional sonata practices. From a stylistic perspective, the works engage with a range of international aesthetic discourses, constantly repositioned within the post-colonial, South African zeitgeist. The sonata’s prominent position in South African art music is not only reflected in the historically high frequency of its use, but also in the ways the sonata paradigm is continuously being reinvented, deconstructed and developed to reflect the country’s idiosyncratic and dynamic cultural identity